Catalyst for preparing aviation kerosene fraction hydrocarbons from synthesis gas and application of catalyst
By loading metal cobalt and additives on the carbon-based material, combined with calcining, reduction and carbonization reduction and transformation treatment, a catalyst with a nanopore structure was prepared, which solved the problem of insufficient selectivity of Fischer-Tropsch synthesis catalysts and achieved the effect of efficient production of C10-C17 aerospace coal fraction hydrocarbons.
Patent Information
- Application Number
- CN202510476512.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-16
- Publication Date
- 2025-07-25
AI Technical Summary
It is difficult for the existing Fischer Tropsch synthesis catalyst to produce C10 to C17 highly selectively. The carbon number distribution of traditional catalysts is too wide, which affects the efficiency of syngas-made air coal fraction hydrocarbons.
Supported catalysts are used, with carbon-based materials as support, metal cobalt as active components, and additives are one or more of zirconium, chromium, manganese, nickel, zinc, and yttrium. Through equal volume impregnation, calcination, reduction and carbonization reduction and transformation treatment, catalysts with nanopore structures are prepared to limit the growth of the carbon chain and improve catalytic activity.
The activity of Fischer-Tropsch synthesis and the selectivity of C10~C17 hydrocarbons are significantly improved, and the efficiency of hydrocarbons made from synthesis gas is improved.
Smart Images

Figure BDA0005361489640000161 
Figure BDA0005361489640000171
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of catalysis, and particularly relates to a catalyst for synthesizing syngas into jet fuel fraction hydrocarbons and its application. Background Art
[0002] Sustainable Aviation Fuel (SAF) refers to aviation fuel synthesized from renewable resources, waste, carbon dioxide, etc. as raw materials and passing airworthiness certification and sustainable certification. Its energy density and volume density are basically the same as those of traditional aviation kerosene, and it can be well compatible with existing aircraft and civil aviation infrastructure. Moreover, low-carbon emissions can be achieved throughout the life cycle through carbon capture and storage in the raw material planting and collection stages. Sustainable aviation fuel can also be an alternative fuel produced in a sustainable manner from waste animal and vegetable oils, oils, used cooking oil, municipal solid waste, and agricultural and forestry waste. It can also be produced through multiple technical routes such as using the above raw materials to produce ethanol by biological fermentation, dehydrating ethanol to produce ethylene, polymerizing ethylene to jet fuel fraction hydrocarbons, and post-processing to SAF. Compared with traditional fossil fuels, the carbon emissions generated during the entire process of SAF from raw material collection to end-user use can be reduced by up to 75%.
[0003] Fischer-Tropsch synthesis (or Fischer-Tropsch process) refers to the reaction process in which syngas obtained from coal, natural gas, and biomass gasification synthesizes hydrocarbons and oxygen-containing compounds under high temperature and pressure and the action of metal catalysts (iron, cobalt, ruthenium, etc.). The products that may be obtained from Fischer-Tropsch synthesis include hydrocarbon products such as light hydrocarbon gases and liquid fuels (naphtha, diesel), as well as paraffin wax and oxygen-containing compounds (such as alcohols, aldehydes, etc.). Carbon-one chemical engineering technology, which is developed with the conversion of syngas into energy products as a representative, will play a very important role in energy chemical engineering, especially in the production of SAF. The production route of using sustainable green syngas to be highly selectively converted into jet fuel fraction hydrocarbons and then post-treated and upgraded into SAF technology is expected to replace the traditional production route of jet fuel based on petroleum, and has great theoretical research significance and strategic significance.
[0004] Using biomass, including herbaceous plants and municipal kitchen waste, etc., to produce green syngas through gasification, and then highly selectively producing C 10 ~C 17 jet fuel fraction hydrocarbons, and post-treating and upgrading them into SAF, which meets the standards of sustainable aviation kerosene. Moreover, this process has low carbon emissions, rich raw material sources, relatively mature synthesis process technology, and is also easy to achieve large-scale production, and has broad application prospects. To achieve the high-selectivity production of C 10 ~C 17The core key of fractionated hydrocarbons is an efficient Fischer-Tropsch synthesis catalyst. The hydrocarbon products prepared by traditional Fischer-Tropsch synthesis have a relatively wide carbon number range, and the typical carbon numbers of Fischer-Tropsch synthesized hydrocarbons range from C1 to C 100 and are all distributed. Therefore, developing efficient catalysts, reasonably regulating the chain growth factor, and increasing the selectivity of C 10 ~C 17 hydrocarbons in the Fischer-Tropsch synthesis products are the research focus of synthesizing jet fuel fractionated hydrocarbons from syngas through the Fischer-Tropsch synthesis route. To achieve this goal, the catalyst provided by the present invention has active metal nanoparticles in the nanopores of the carbon-based support, and the carbon chain growth in the Fischer-Tropsch synthesis is restricted to a certain extent by the spatial structure of the catalyst pores; at the same time, different crystal forms of metallic cobalt, especially metallic cobalt (hcp-Co) nanoparticles with a hexagonal close-packed phase, can improve the Fischer-Tropsch synthesis activity of the catalyst and reduce the production of light hydrocarbons. Summary of the Invention
[0005] The specific technical solution is as follows:
[0006] A catalyst for synthesizing jet fuel fractionated hydrocarbons from syngas, which is a supported catalyst. The support is a carbon-based material, and the active component supported on the support is metallic cobalt. The weight of metallic cobalt accounts for 8.0 - 30.0 wt% (preferably 9.0 - 25.0 wt%, more preferably 11.0 - 24.0 wt%) of the weight of the catalyst;
[0007] The support also supports a promoter, and the weight of the promoter accounts for 0.6 - 4.0 wt% (preferably 0.6 - 3.5 wt%, more preferably 1.0 - 3.0 wt%) of the weight of the catalyst, and the promoter is one or more of zirconium, chromium, manganese, nickel, zinc, and yttrium;
[0008] The active component and the promoter are loaded onto the support by incipient wetness impregnation, and then the catalyst precursor is prepared into an activated metal catalyst through calcination, reduction, and carbonization reduction and crystal transformation treatment. The specific preparation process is as follows:
[0009] (1) Using the carbon-based material as the support, a mixed solution prepared from an aqueous solution composed of a soluble cobalt salt, a soluble promoter salt, and a water-soluble organic matter is impregnated on the support by incipient wetness, and the catalyst precursor is obtained after drying;
[0010] In the impregnation solution during the catalyst preparation process, the weight of the water-soluble organic matter accounts for 0.01 - 5.0 wt% (preferably 0.05 - 4.5 wt%, more preferably 0.08 - 4.0 wt%) of the weight of the support; the water-soluble organic matter contains two components. The first component is hydroxyethyl cellulose, and the second component is one or more of ethylene glycol, diethylene glycol, 1,2-propanediol, 1,3-propanediol, glycerol, 1,4-butanediol, xylitol, sorbitol, and pentaerythritol; the mass ratio of the first component to the second component is 1:1 - 1:10 (preferably 1:1 - 1:8, more preferably 1:1 - 1:5);
[0011] (2) Calcination: The catalyst precursor is first calcined in an inert atmosphere. The calcination temperature is 150 - 450 °C (preferably 200 - 430 °C, more preferably 200 - 400 °C), the pressure is 0.1 - 0.6 MPa (preferably 0.1 - 0.5 MPa, more preferably 0.1 - 0.4 MPa), and the gas hourly space velocity is 300 - 1500 h -1 (preferably 300 - 1300 h -1 , more preferably 400 - 1000 h -1 ), and the calcination time is 6 - 30 hours (preferably 6 - 24 hours, more preferably 10 - 24 hours);
[0012] (3) Reduction: After calcination, the catalyst precursor is switched to a hydrogen-containing atmosphere for reduction. The hydrogen-containing atmosphere is hydrogen or a mixture of hydrogen and an inert gas. The volume content of hydrogen in the hydrogen-containing atmosphere is 1% - 100% (preferably 5% - 95%, more preferably 9% - 90%); the reduction temperature is 300 - 650 °C (preferably 300 - 550 °C, more preferably 350 - 500 °C), the pressure is 0.1 - 1.0 MPa (preferably 0.1 - 0.8 MPa, more preferably 0.2 - 0.7 MPa), and the gas hourly space velocity is 300 - 1500 h -1 (preferably 300 - 1300 h -1 , more preferably 400 - 1000 h -1 ), and the reduction time is 10 - 60 hours (preferably 10 - 50 hours, more preferably 15 - 45 hours);
[0013] (4) Carbonization reduction and crystal transformation:
[0014] ① After reduction, the catalyst precursor is switched to a carbon monoxide-containing atmosphere for carbonization. The carbon monoxide-containing atmosphere is a mixture of carbon monoxide and an inert gas. The volume content of carbon monoxide in the carbon monoxide-containing atmosphere is 1 - 100% (preferably 5% - 95%, more preferably 9% - 90%); the carbonization temperature is 150 - 350 °C (preferably 170 - 320 °C, more preferably 180 - 250 °C), the pressure is 0.5 - 5.0 MPa (preferably 1.0 - 4.5 MPa, more preferably 1.0 - 4.0 MPa), and the gas hourly space velocity is 500 - 3000 h -1 (preferably 500 - 2500 h -1 , more preferably 600 - 2500 h -1 ), and the carbonization time is 10 - 60 hours (preferably 10 - 50 hours, more preferably 15 - 45 hours);
[0015] ② After carbonization, switch to a hydrogen-containing atmosphere for reduction treatment. The hydrogen-containing atmosphere is hydrogen or a mixture of hydrogen and an inert gas. The volume content of hydrogen in the hydrogen-containing atmosphere is 1 to 100% (preferably 5% to 95%, more preferably 9% to 90%); the reduction temperature is 150 to 350 °C (preferably 300 to 550 °C, more preferably 180 to 250 °C), the pressure is 0.5 to 5.0 MPa (preferably 1.0 to 4.5 MPa, more preferably 1.0 to 4.0 MPa), and the gas hourly space velocity is 500 to 3000 h -1 (preferably 500 to 2500 h -1 , more preferably 600 to 2500 h -1 ), and the reduction time is 10 to 60 hours (preferably 10 to 50 hours, more preferably 15 to 45 hours).
[0016] The soluble cobalt salt is one or more of cobalt nitrate, cobalt phosphate, cobalt acetate, cobalt citrate, and cobalt malate; the soluble promoter salt is one or more of nitrates, sulfates, phosphates, and citrates of one or more of zirconium, chromium, manganese, nickel, zinc, and yttrium.
[0017] In the step (1), using a carbon-based material as a carrier, a mixed solution prepared from an aqueous solution composed of a soluble cobalt salt, a soluble promoter salt, and a water-soluble organic matter is impregnated on the carrier in an equal volume, and left standing at room temperature for 6 to 18 hours (preferably 6 to 16 hours, more preferably 8 to 16 hours), and then dried in an air atmosphere at a temperature of 40 to 100 °C (preferably 40 to 95 °C, more preferably 45 to 95 °C) for 6 to 24 hours (preferably 6 to 20 hours, more preferably 8 to 20 hours) to obtain a catalyst precursor.
[0018] The inert gas is one or more of nitrogen, argon, and helium;
[0019] The reactors used in the steps (2), (3), and (4) for roasting, reduction, and carbonization reduction and crystal transformation are fixed-bed reactors or fixed-fluidized bed reactors.
[0020] The carbon-based material is a carbon-based material with a nanoporous structure. The carbon-based material needs to be pretreated before use. The pretreatment process includes the following steps:
[0021] Using a commercially available carbon-based material with a pore size distribution of 0.1 to 80 nm as a raw material, including one or more of activated carbon, ordered mesoporous carbon, silicon carbide, and activated nitrogen-doped carbon with a nitrogen mass content of 3% to 20% (preferably 3% to 18%, more preferably 4% to 18%), and performing the following treatment:
[0022] (1) Perform pore expansion treatment on the carbon-based material in a specific atmosphere: The treatment gas is one or more of oxygen, carbon monoxide, carbon dioxide, and water vapor. The treatment temperature is 400 - 800 °C (preferably 450 - 750 °C, more preferably 480 - 720 °C), the treatment pressure is 0.1 - 1.0 MPa (preferably 0.1 - 0.8 MPa, more preferably 0.2 - 0.7 MPa), and the treatment time is 1 - 24 hours (preferably 1 - 20 hours, more preferably 2 - 20 hours);
[0023] (2) Perform modification treatment on the carbon-based material obtained in step (1): The solution for modification treatment is an aqueous solution of one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, ammonia with a mass concentration of 1% - 20% (preferably 1% - 18%, more preferably 3% - 18%) or an ethanol solution of one or more of dicyandiamide, melamine, ethylenediamine with a mass concentration of 1% - 20% (preferably 1% - 18%, more preferably 3% - 18%). The weight ratio of the solution to the carbon-based material is 2:1 - 20:1 (preferably 3:1 - 20:1, more preferably 3:1 - 18:1). The treatment temperature is 40 - 100 °C (preferably 40 - 90 °C, more preferably 45 - 90 °C), and the treatment time is 1 - 24 hours (preferably 2 - 24 hours, more preferably 2 - 20 hours);
[0024] (3) Perform water washing and impurity removal treatment on the carbon-based material obtained in step (2): The water washing temperature is 20 - 100 °C (preferably 25 - 95 °C, more preferably 30 - 95 °C), wash until pH = 7, and obtain a carbon-based support after drying. The treated carbon-based material needs to meet the following requirements: The pore size distribution is 2 - 100 nm, and the proportion of the number of pores with a pore size of 5 - 25 nm reaches more than 70%.
[0025] The application of the catalyst in the synthesis of syngas to jet fuel fraction hydrocarbons. The reactor is a fixed-bed reactor, a slurry-bed reactor, or a fixed fluidized-bed reactor. The raw material gas is syngas (a mixture of H2 and CO). Under the reaction conditions of an H2 / CO molar ratio of 1.0 - 4.0 (preferably 1.4 - 3.5, more preferably 1.7 - 3.5), a reaction temperature of 180 - 280 °C (preferably 180 - 260 °C, more preferably 190 - 250 °C), a pressure of 1.0 - 8.0 MPa (preferably 1.0 - 7.0 MPa, more preferably 1.5 - 7.0 MPa), and a gas hourly space velocity of 500 - 8000 h -1 (preferably 500 - 6000 h -1 , more preferably 800 - 6000 h -1 ), carry out the reaction of synthesizing syngas to jet fuel fraction hydrocarbons. The reaction tail gas and products are continuously discharged. The generated liquid products are first collected by a hot tank for its heavy components, and then collected by a cold trap for its light components. The temperature of the hot tank is maintained at 110 - 130 °C, and the temperature of the cold trap is maintained at 0 - 5 °C.
[0026] Using the catalyst provided by the present invention can significantly improve the Fischer-Tropsch synthesis activity and the selectivity of C 10 ~C 17 hydrocarbons. Detailed implementation manners
[0027] Example 1
[0028] The composition of catalyst A is 20Co3Cr / AC. Among them, the weight percentage content of metal Co is 20 wt%, and the weight percentage content of promoter Cr is 3.0 wt%. Using activated carbon with a particle size of 20-40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol and glycerol. The catalyst is prepared according to the following steps.
[0029] 1. The pretreatment method of activated carbon is as follows:
[0030] The specific surface area of the activated carbon is measured by N2 physical adsorption to be 1000 m 2 / g, the pore volume is 0.8 mL / g, and the pore size distribution is in the range of 0.3-50 nm. Among them, the pores with a pore size of 0.3-5 nm account for 50%, the pores with a pore size greater than 5 nm-25 nm account for 30%, and the pores with a pore size greater than 25 nm-50 nm account for 20%.
[0031] (1) The carbon-based material is subjected to pore expansion treatment: the treatment gas is water vapor, the treatment temperature is 500 °C, the treatment time is 12 hours, and the pressure is 0.3 MPa;
[0032] (2) The carbon-based material obtained in step (1) is subjected to surface modification treatment: the solution used for surface modification treatment is a 10% nitric acid aqueous solution, and the weight ratio of the solution to the carbon-based material is 10:1. The treatment temperature is 60 °C, and the treatment time is 12 hours;
[0033] (3) The carbon-based material obtained in step (2) is subjected to water washing and impurity removal treatment: the water washing temperature is 90 °C, washed until neutral, and the carbon-based carrier is obtained after drying.
[0034] The specific surface area of the pretreated activated carbon carrier is measured by N2 physical adsorption to be 1500 m 2 / g, the pore volume is 1.2 mL / g, and the pore size distribution is in the range of 5-53 nm. Among them, the pores with a pore size of 5-25 nm account for 72%, and the pores with a pore size greater than 25 nm-53 nm account for 28%.
[0035] 2. The catalyst preparation method is as follows:
[0036] Weigh 12.4 g of cobalt nitrate hexahydrate and dissolve it in 6 g of deionized water, 2.0 g of chromium nitrate nonahydrate and dissolve it in 3 g of deionized water, 0.1 g of hydroxyethyl cellulose, 0.1 g of ethylene glycol and 0.1 g of glycerol and dissolve them in 1 g of deionized water. Mix the three solutions thoroughly. Weigh 10 g of activated carbon and use the equal-volume impregnation method to load the mixed solution onto the activated carbon support. Let it stand at room temperature for 10 hours and then dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0037] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and phase transformation treatment. The specific steps are as follows:
[0038] (1) Calcination: Pass argon for calcination at a pressure of 0.1 MPa and a gas hourly space velocity of 600 h -1 , at a calcination temperature of 350 °C and a calcination time of 12 hours;
[0039] (2) Reduction: After cooling to room temperature, switch to a mixture of hydrogen and argon (volume ratio 1:9) for reduction treatment at a pressure of 0.3 MPa and a gas hourly space velocity of 600 h -1 , at a reduction temperature of 400 °C and a time of 24 hours;
[0040] (3) Carbonization reduction and phase transformation: After cooling to room temperature, switch to a mixture of carbon monoxide and argon (volume ratio 1:1) for reduction treatment. The carbonization temperature is 230 °C, the pressure is 4.0 MPa, and the gas hourly space velocity is 1000 h -1 , and the carbonization time is 30 hours. After carbonization, without cooling down, switch to a mixture of hydrogen and argon (volume ratio 1:1) for reduction. The reduction temperature is 230 °C, the pressure is 4.0 MPa, and the gas hourly space velocity is 1000 h -1 , and the reduction time is 30 hours.
[0041] The activated catalyst A is prepared. By ICP-OES analysis, the weight percentage of metallic Co in the catalyst is 20.5 wt% (calculated as metal), and the weight percentage of the promoter Cr is 3.1 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst is in the range of 6 - 8 nm.
[0042] 3. The catalyst evaluation method is as follows:
[0043] Use a slurry bed reactor to evaluate the activated catalyst A for the reaction of syngas to aviation kerosene fraction hydrocarbons under the reaction conditions of a H2 / CO molar ratio of 2.0, a reaction temperature of 220 °C, a pressure of 3.0 MPa, and a syngas hourly space velocity of 2000 h -1 . The reaction tail gas and products are continuously discharged. The generated liquid products are first collected by a hot tank for their heavy components and then by a cold trap for their light components. The temperature of the hot tank is maintained at 120 °C, and the temperature of the cold trap is maintained at 5 °C.
[0044] Example 2
[0045] The composition of catalyst B is 15Co2Zr / SiC. Among them, the weight percentage of metallic Co is 15 wt%, and the weight percentage of promoter Zr is 2.0 wt%. Using silicon carbide with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, diethylene glycol, and glycerol. The catalyst is prepared according to the following steps.
[0046] 1. The pretreatment method of silicon carbide is as follows:
[0047] The specific surface area of silicon carbide measured by N2 physical adsorption is 230 m 2 / g, the pore volume is 0.6 mL / g, and the pore size distribution is in the range of 3 - 30 nm. Among them, the pores with a pore size of 3 - 5 nm account for 30%, the pores with a pore size greater than 5 nm - 25 nm account for 50%, and the pores with a pore size greater than 25 nm - 30 nm account for 20%.
[0048] (1) Perform pore expansion treatment on the carbon-based material: the same as step 1(1) in Example 1;
[0049] (2) Perform surface modification treatment on the carbon-based material obtained in step (1): the solution for surface modification treatment is a 10% aqueous nitric acid solution, the weight ratio of the solution to the carbon-based material is 10:1, the treatment temperature is 80 °C, and the treatment time is 12 hours;
[0050] (3) Perform water washing and impurity removal treatment on the carbon-based material obtained in step (2): the same as step 1(3) in Example 1.
[0051] The specific surface area of the treated silicon carbide carrier measured by N2 physical adsorption is 350 m 2 / g, the pore volume is 0.7 mL / g, and the pore size distribution is in the range of 10 - 33 nm. Among them, the pores with a pore size of 10 - 25 nm account for 72%, and the pores with a pore size greater than 15 - 33 nm account for 28%.
[0052] 2. The catalyst preparation method is as follows:
[0053] Weigh 9.0 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 1.5 grams of zirconium nitrate pentahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of diethylene glycol, and 0.1 gram of glycerol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of silicon carbide, and use the equal-volume impregnation method to load the mixed solution on the silicon carbide carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0054] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and phase transformation treatment. The specific steps are as follows: (1) Calcination: the same as step (1) in step 2 of Example 1;
[0055] (2) Reduction: the same as step (2) in step 2 of Example 1;
[0056] (3) Carbonization reduction and phase transformation: the same as step (3) in step 2 of Example 1.
[0057] The activated catalyst B is obtained. By ICP-OES analysis, the weight percentage of metallic Co in the catalyst is 14.5 wt% (calculated as metal), and the weight percentage of the promoter Zr is 1.8 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst is distributed in the range of 9 - 14 nm.
[0058] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0059] Example 3
[0060] The composition of catalyst C is 15Co1Mn / NC, where the weight percentage of metallic Co is 15 wt%, and the weight percentage of the promoter Mn is 1.0 wt%. Using nitrogen-doped activated carbon (nitrogen content 6%) with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, and sorbitol. The catalyst is prepared according to the following steps.
[0061] 1. The pretreatment method of the nitrogen-doped activated carbon is as follows:
[0062] The specific surface area of the treated nitrogen-doped activated carbon carrier is measured by N2 physical adsorption to be 850 m 2 / g, the pore volume is 0.6 mL / g, and the pore size distribution is in the range of 0.1 - 30 nm, where the pores with a pore size of 0.1 - 3 nm account for 25%, the pores with a pore size greater than 3 nm - 25 nm account for 45%, and the pores with a pore size greater than 25 nm - 30 nm account for 30%.
[0063] (1) Perform pore expansion treatment on the carbon-based material: the same as step (1) in Example 1;
[0064] (2) Perform surface modification treatment on the carbon-based material obtained in step (1): the same as step (2) in Example 1;
[0065] (3) Perform water washing and impurity removal treatment on the carbon-based material obtained in step (2): the same as step (3) in Example 1.
[0066] The specific surface area of the treated nitrogen-doped activated carbon carrier is measured by N2 physical adsorption to be 1050 m 2 / g, pore volume 0.8 mL / g, pore size distribution is 5 - 32 nm, among which the pores with pore size of 5 - 25 nm account for 71%, and the pores with pore size greater than 15 nm - 32 nm account for 29%.
[0067] 2. The catalyst preparation method is as follows:
[0068] Weigh 8.9 grams of cobalt nitrate hexahydrate and dissolve it in 8 grams of deionized water, 1.3 grams of 50 wt% manganese nitrate solution, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol and 0.1 gram of sorbitol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of nitrogen-doped activated carbon, and use the equal-volume impregnation method to load the mixed solution on the nitrogen-doped activated carbon support. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0069] Subsequently, the catalyst precursor is subjected to calcination, reduction and carbonization reduction and crystal transformation treatment. The specific steps are as follows: (1) Calcination: the same as step 2(1) in Example 1;
[0070] (2) Reduction: the same as step 2(2) in Example 1;
[0071] (3) Carbonization reduction and crystal transformation: the same as step 2(3) in Example 1.
[0072] The activated catalyst C is prepared. By ICP analysis, the weight percentage of metal Co in the catalyst is 14.8 wt% (calculated as metal), and the weight percentage of the promoter Mn is 0.9 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of metal nanoparticles on the catalyst is 8 - 11 nm.
[0073] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0074] Example 4
[0075] The composition of catalyst D is 15Co1Zn / OMCs. Among them, the weight percentage of metal Co is 15 wt%, and the weight percentage of the promoter Zn is 1.0 wt%. Using ordered mesoporous carbon CMK-3 with a particle size of 20 - 40 mesh as the carrier, and the water-soluble organic substances used are hydroxyethyl cellulose, glycerol and sorbitol. The catalyst is prepared according to the following steps.
[0076] 1. The pretreatment method of ordered mesoporous carbon is as follows:
[0077] The specific surface area of the treated ordered mesoporous carbon support is measured by N2 physical adsorption to be 850 m 2 / g, pore volume 0.8 mL / g, pore size distribution ranging from 2 to 20 nm, where the pores with a pore size of 2 to 5 nm account for 35%, the pores with a pore size greater than 3 nm to 10 nm account for 45%, and the pores with a pore size greater than 10 nm to 20 nm account for 20%.
[0078] (1) Pretreat the ordered mesoporous carbon: same as step (1) in Example 1;
[0079] (2) Perform surface modification on the carbon-based material obtained in step (1): same as step (2) in Example 1;
[0080] (3) Perform water washing and impurity removal on the carbon-based material obtained in step (2): same as step (3) in Example 1.
[0081] The specific surface area of the treated ordered mesoporous carbon support was measured by N2 physical adsorption to be 1000 m 2 / g, pore volume 1.0 mL / g, pore size distribution ranging from 6 to 22 nm, where the pores with a pore size of 6 to 10 nm account for 75%, and the pores with a pore size greater than 10 nm to 22 nm account for 25%.
[0082] 2. The catalyst preparation method is as follows:
[0083] Weigh 8.9 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 1.0 gram of zinc nitrate hexahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol and 0.1 gram of sorbitol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of ordered mesoporous carbon, and use the equal-volume impregnation method to load the mixed solution on the ordered mesoporous carbon support. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0084] Subsequently, perform calcination, reduction, and carbonization reduction and crystal transformation on the catalyst precursor. The specific steps are as follows: (1) Calcination: same as step (1) in step 2 of Example 1;
[0085] (2) Reduction: same as step (2) in step 2 of Example 1;
[0086] (3) Carbonization reduction and crystal transformation: same as step (3) in step 2 of Example 1.
[0087] The activated catalyst D is prepared. By ICP analysis, the weight percentage of metal Co in the catalyst is 15.3 wt% (calculated as metal), and the weight percentage of the promoter Zn is 1.1 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst is in the range of 10 to 15 nm.
[0088] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0089] Example 5
[0090] The composition of catalyst E is 15Co1Ni / AC. Among them, the weight percentage of metallic Co is 15 wt%, and the weight percentage of promoter Ni is 1.0 wt%. Using activated carbon with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, and pentaerythritol. The catalyst is prepared according to the following steps.
[0091] 1. The pretreatment method of the activated carbon is the same as step 1 in Example 1.
[0092] 2. The catalyst preparation method is as follows:
[0093] Weigh 8.9 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 1.0 gram of nickel nitrate hexahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol, and 0.1 gram of pentaerythritol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of activated carbon, and use the equal-volume impregnation method to load the mixed solution onto the activated carbon carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0094] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and crystal transformation treatments. The specific steps are as follows: (1) Calcination: the same as (1) in step 2 of Example 1;
[0095] (2) Reduction: the same as (2) in step 2 of Example 1;
[0096] (3) Carbonization reduction and crystal transformation: the same as (3) in step 2 of Example 1.
[0097] The activated catalyst E is obtained. Through ICP analysis, the weight percentage of metallic Co in the catalyst is 14.8 wt% (calculated as metal), and the weight percentage of promoter Mn is 0.9 wt% (calculated as metal). Through HRTEM analysis, the particle size of the catalyst is distributed between 8 - 11 nm.
[0098] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0099] Example 6
[0100] The composition of catalyst F is 15Co2Zr / SiC. Among them, the weight percentage of metallic Co is 15 wt%, and the weight percentage of promoter Zr is 2.0 wt%. Using silicon carbide with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, diethylene glycol, and pentaerythritol. The catalyst is prepared according to the following steps.
[0101] 1. The pretreatment method of the silicon carbide is the same as step 1 in Example 2.
[0102] 2. The catalyst preparation method is as follows:
[0103] Weigh 9.0 g of cobalt nitrate hexahydrate and dissolve it in 5 g of deionized water, 1.5 g of zirconium nitrate pentahydrate and dissolve it in 4 g of deionized water, 0.1 g of hydroxyethyl cellulose, 0.07 g of ethylene glycol, 0.07 g of diethylene glycol and 0.06 g of pentaerythritol and dissolve them in 1 g of deionized water. Then mix the three solutions thoroughly. Weigh 10 g of silicon carbide and use the equal-volume impregnation method to load the mixed solution onto the silicon carbide support. Let it stand at room temperature for 10 hours and then dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0104] Subsequently, the catalyst precursor is subjected to calcination, reduction and carbonization reduction and crystal transformation treatment. The specific steps are as follows: (1) Calcination: the same as step (1) of step 2 in Example 1;
[0105] (2) Reduction: the same as step (2) of step 2 in Example 1;
[0106] (3) Carbonization reduction and crystal transformation: the same as step (3) of step 2 in Example 1.
[0107] The activated catalyst F is prepared. By ICP analysis, the weight percentage of metal Co in the catalyst is 15.3 wt% (calculated as metal), and the weight percentage of the promoter Zr is 2.2 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst is distributed in the range of 13 - 17 nm.
[0108] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0109] Example 7
[0110] The composition of catalyst G is 15Co1Mn1Ni / AC. Among them, the weight percentage of metal Co is 15 wt%, the weight percentage of the promoter Mn is 1.0 wt%, and the weight percentage of the promoter Ni is 1.0 wt%. Using activated carbon with a particle size of 20 - 40 mesh as the carrier, and the water-soluble organic substances used are hydroxyethyl cellulose, glycerol, sorbitol and pentaerythritol. The catalyst is prepared according to the following steps.
[0111] 1. The pretreatment method of the activated carbon is the same as step 1 in Example 1.
[0112] 2. The catalyst preparation method is as follows:
[0113] Weigh 8.9 g of cobalt nitrate hexahydrate and dissolve it in 5 g of deionized water, 1.3 g of 50 wt% manganese nitrate solution, and 1.0 g of nickel nitrate hexahydrate and dissolve it in 4 g of deionized water. Dissolve 0.1 g of hydroxyethyl cellulose, 0.06 g of glycerol, 0.06 g of sorbitol, and 0.08 g of pentaerythritol in 1 g of deionized water. Mix the three solutions thoroughly. Weigh 10 g of activated carbon, and use the equal-volume impregnation method to load the mixed solution onto the activated carbon support. Let it stand at room temperature for 10 hours, and then dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0114] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and crystal transformation treatments. The specific steps are as follows: (1) Calcination: the same as step (1) of step 2 in Example 1;
[0115] (2) Reduction: the same as step (2) of step 2 in Example 1;
[0116] (3) Carbonization reduction and crystal transformation: the same as step (3) of step 2 in Example 1.
[0117] The activated catalyst G is prepared. By ICP analysis, the weight percentage of metal Co in the catalyst is 15.0 wt% (calculated as metal), the weight percentage of promoter Mn is 0.8 wt% (calculated as metal), and the weight percentage of promoter Ni is 0.9 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst is distributed in the range of 7 - 10 nm.
[0118] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0119] Comparative Example 1
[0120] The composition of catalyst H is 20Co3Cr / AC. Among them, the weight percentage of metal Co is 20 wt%, and the weight percentage of promoter Cr is 3.0 wt%. Using commercially available activated carbon with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, and glycerol. The catalyst is prepared according to the following steps.
[0121] 1. Using commercially available activated carbon as the catalyst carrier, no pretreatment is carried out. The specific surface area of the activated carbon is measured by N2 physical adsorption to be 1000 m 2 / g, the pore volume is 0.8 mL / g, and the pore size distribution is in the range of 0.3 - 50 nm. Among them, the pores with a pore size of 0.3 - 5 nm account for 50%, the pores with a pore size greater than 5 nm - 25 nm account for 30%, and the pores with a pore size greater than 25 nm - 50 nm account for 20%.
[0122] 2. The catalyst preparation method is as follows:
[0123] Weigh 12.4 g of cobalt nitrate hexahydrate and dissolve it in 5 g of deionized water, 2.0 g of chromium nitrate nonahydrate and dissolve it in 4 g of deionized water, 0.1 g of hydroxyethyl cellulose, 0.1 g of ethylene glycol and 0.1 g of glycerol and dissolve them in 1 g of deionized water. Mix the three solutions thoroughly. Weigh 10 g of activated carbon, and use the equal-volume impregnation method to load the mixed solution onto the activated carbon carrier. Let it stand at room temperature for 10 hours and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0124] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and crystal transformation treatments. The specific steps are as follows:
[0125] (1) Calcination: the same as (1) in step 2 of Example 1;
[0126] (2) Reduction: the same as (2) in step 2 of Example 1;
[0127] (3) Carbonization reduction and crystal transformation: the same as (3) in step 2 of Example 1.
[0128] The activated catalyst H is prepared. By ICP analysis, the weight percentage of metal Co in the catalyst is 19.8 wt% (calculated as metal), and the weight percentage of the promoter Cr is 2.9 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst is distributed in the range of 10 - 15 nm.
[0129] 3. The catalyst evaluation method is the same as that in step 3 of Example 1.
[0130] Comparative Example 2
[0131] The composition of catalyst I is 20Co3Cr / AC. Among them, the weight percentage of metal Co is 20 wt%, and the weight percentage of the promoter Cr is 3.0 wt%. Using commercially available activated carbon with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, and glycerol. The catalyst is prepared according to the following steps.
[0132] 1. Using commercially available activated carbon as the catalyst carrier, the same as step 1 in Comparative Example 1.
[0133] 2. The catalyst preparation method is as follows:
[0134] Weigh 12.4 g of cobalt nitrate hexahydrate and dissolve it in 5 g of deionized water, 2.0 g of chromium nitrate nonahydrate and dissolve it in 4 g of deionized water, 0.1 g of hydroxyethyl cellulose, 0.1 g of ethylene glycol and 0.1 g of glycerol and dissolve them in 1 g of deionized water. Mix the three solutions thoroughly. Weigh 10 g of activated carbon, and use the equal-volume impregnation method to load the mixed solution onto the activated carbon carrier. Let it stand at room temperature for 10 hours and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0135] Subsequently, the catalyst precursor was calcined and reduced, and the specific steps are as follows:
[0136] (1) Calcination: the same as (1) in Step 2 of Example 1;
[0137] (2) Reduction: the same as (2) in Step 2 of Example 1;
[0138] The activated catalyst I was obtained. By ICP analysis, the weight percentage of metal Co in the catalyst was 19.8 wt% (calculated as metal), and the weight percentage of the promoter Cr was 2.9 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst was distributed in the range of 10 - 15 nm.
[0139] 3. The catalyst evaluation method was the same as that in Step 3 of Example 1.
[0140] Comparative Example 3
[0141] The composition of catalyst J was 20Co3Cr / AC, where the weight percentage of metal Co was 20 wt%, and the weight percentage of the promoter Cr was 3.0 wt%. Using commercially available activated carbon with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic matter used was hydroxyethyl cellulose, and the catalyst was prepared according to the following steps.
[0142] 1. The pretreatment method of the activated carbon was the same as that in Step 1 of Example 1.
[0143] 2. The catalyst preparation method was as follows:
[0144] 12.4 g of cobalt nitrate hexahydrate was dissolved in 5 g of deionized water, 2.0 g of chromium nitrate nonahydrate was dissolved in 4 g of deionized water, and 0.1 g of hydroxyethyl cellulose was dissolved in 1 g of deionized water. The three solutions were fully mixed evenly. 10 g of activated carbon was weighed, and the mixed solution was loaded onto the activated carbon carrier by the equal-volume impregnation method. It was left standing at room temperature for 10 hours and dried in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0145] Subsequently, the catalyst precursor was subjected to calcination, reduction, and carbonization reduction and crystal transformation treatment, and the specific steps are as follows:
[0146] (1) Calcination: the same as (1) in Step 2 of Example 1;
[0147] (2) Reduction: the same as (2) in Step 2 of Example 1;
[0148] (3) Carbonization reduction and crystal transformation: the same as (3) in Step 2 of Example 1.
[0149] The activated catalyst J was prepared. By ICP analysis, the weight percentage of metallic Co in the catalyst was 20.4 wt% (calculated as metal), and the weight percentage of promoter Cr was 3.1 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst was in the range of 15 - 25 nm.
[0150] 3. The catalyst evaluation method was the same as that in Step 3 of Example 1.
[0151] Comparative Example 4
[0152] The composition of catalyst K was 20Co3Cr / AC. Among them, the weight percentage of metallic Co was 20 wt%, and the weight percentage of promoter Cr was 3.0 wt%. Using commercially available activated carbon with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic matter used was hydroxyethyl cellulose, and the catalyst was prepared according to the following steps.
[0153] 1. The pretreatment method of the activated carbon was the same as that in Step 1 of Example 1.
[0154] 2. The catalyst preparation method was as follows:
[0155] Weighed 12.4 g of cobalt nitrate hexahydrate and dissolved it in 5 g of deionized water, and 2.0 g of chromium nitrate nonahydrate and dissolved it in 4 g of deionized water. The two solutions were fully mixed evenly. Weighed 10 g of activated carbon, and the mixed solution was loaded onto the activated carbon carrier by the equal-volume impregnation method. It was left standing at room temperature for 10 hours and then dried in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0156] Subsequently, the catalyst precursor was subjected to calcination, reduction, and carbonization reduction and crystal transformation treatment. The specific steps were as follows:
[0157] (1) Calcination: the same as (1) in Step 2 of Example 1;
[0158] (2) Reduction: the same as (2) in Step 2 of Example 1;
[0159] (3) Carbonization reduction and crystal transformation: the same as (3) in Step 2 of Example 1.
[0160] The activated catalyst K was prepared. By ICP analysis, the weight percentage of metallic Co in the catalyst was 20.2 wt% (calculated as metal), and the weight percentage of promoter Cr was 3.0 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst was in the range of 20 - 35 nm.
[0161] 3. The catalyst evaluation method was the same as that in Step 3 of Example 1.
[0162] Comparative Example 5
[0163] The composition of catalyst B is 15Co2Zr / SiC. Among them, the weight percentage of metallic Co is 15 wt%, and the weight percentage of promoter Zr is 2.0 wt%. Using commercially available silicon carbide with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, diethylene glycol, and glycerol. The catalyst is prepared according to the following steps.
[0164] 1. Using N2 physical adsorption to determine that the specific surface area of silicon carbide is 230 m 2 / g, the pore volume is 0.6 mL / g, the pore size distribution is in the range of 3 - 30 nm, among which the pores with a pore size of 3 - 5 nm account for 30%, the pores with a pore size greater than 5 nm - 25 nm account for 50%, and the pores with a pore size greater than 25 nm - 30 nm account for 20%.
[0165] 2. The catalyst preparation method is as follows:
[0166] Weigh 9.0 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 1.5 grams of zirconium nitrate pentahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of diethylene glycol, and 0.1 gram of glycerol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of silicon carbide, and use the equal-volume impregnation method to load the mixed solution onto the silicon carbide carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0167] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization-reduction and crystal transformation treatments. The specific steps are as follows:
[0168] (1) Calcination: The same as step (1) in step 2 of Example 1;
[0169] (2) Reduction: The same as step (2) in step 2 of Example 1;
[0170] (3) Carbonization-reduction and crystal transformation: The same as step (3) in step 2 of Example 1.
[0171] The activated catalyst L is prepared. Through ICP analysis, the weight percentage of metallic Co in the catalyst is 14.5 wt% (calculated as metal), and the weight percentage of promoter Zr is 1.8 wt% (calculated as metal). Through HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst is in the range of 20 - 30 nm.
[0172] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0173] Comparative Example 6
[0174] The composition of catalyst D is 15Co1Zn / OMCs, where the weight percentage of metallic Co is 15 wt%, and the weight percentage of promoter Zn is 1.0 wt%. Using ordered mesoporous carbon CMK-3 with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, glycerol, and sorbitol. The catalyst is prepared according to the following steps.
[0175] 1. Using commercially available ordered mesoporous carbon as the catalyst carrier without pretreatment. The specific surface area of the treated ordered mesoporous carbon carrier is measured by N2 physical adsorption to be 850 m 2 / g, the pore volume is 0.8 mL / g, the pore size distribution is in the range of 2 - 20 nm, where the pores with a pore size of 2 - 5 nm account for 35%, the pores with a pore size greater than 3 nm - 10 nm account for 45%, and the pores with a pore size greater than 10 nm - 20 nm account for 20%.
[0176] 2. The catalyst preparation method is as follows:
[0177] Weigh 8.9 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 1.0 gram of zinc nitrate hexahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol, and 0.1 gram of sorbitol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of ordered mesoporous carbon, and use the equal-volume impregnation method to load the mixed solution onto the ordered mesoporous carbon carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0178] Subsequently, the catalyst precursor is subjected to calcination, reduction, and carbonization reduction and phase transformation treatment. The specific steps are as follows:
[0179] (1) Calcination: The same as step (1) in step 2 of Example 1;
[0180] (2) Reduction: The same as step (2) in step 2 of Example 1;
[0181] (3) Carbonization reduction and phase transformation: The same as step (3) in step 2 of Example 1.
[0182] The activated catalyst M is prepared. By ICP analysis, the weight percentage of metallic Co in the catalyst is 19.8 wt% (calculated as metal), and the weight percentage of promoter Cr is 2.9 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst is in the range of 20 - 30 nm.
[0183] 3. The catalyst evaluation method is the same as step 3 in Example 1.
[0184] Comparative Example 7
[0185] The composition of catalyst N is 20Co3Cr / Al2O3. Among them, the weight percentage of metallic Co is 20 wt%, and the weight percentage of promoter Cr is 3.0 wt%. Using commercially available alumina with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used are hydroxyethyl cellulose, ethylene glycol, and glycerol. The catalyst is prepared according to the following steps.
[0186] 1. The pretreatment method of alumina is as follows:
[0187] Using N2 physical adsorption to measure the specific surface area of commercially available alumina is 260 m 2 / g, the pore volume is 0.6 mL / g, the pore size distribution is in the range of 5 - 70 nm, among which the pores with a pore size of 5 - 35 nm account for 65%, and the pores with a pore size greater than 35 - 70 nm account for 35%.
[0188] (1) Pretreat the commercially available alumina: the same as step 1(1) in Example 1;
[0189] (2) Conduct surface modification treatment on the alumina obtained in step (1): the same as step 1(2) in Example 1;
[0190] (3) Conduct water washing and impurity removal treatment on the alumina obtained in step (2): the same as step 1(3) in Example 1.
[0191] Using N2 physical adsorption to measure the specific surface area of the treated activated carbon carrier is 265 m 2 / g, the pore volume is 0.6 mL / g, the pore size distribution is in the range of 6 - 70 nm, among which the pores with a pore size of 6 - 35 nm account for 68%, and the pores with a pore size greater than 35 - 70 nm account for 32%.
[0192] 2. The preparation method of the catalyst is as follows:
[0193] Weigh 12.4 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 2.0 grams of chromium nitrate nonahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol, and 0.1 gram of glycerol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of activated carbon, and use the equal volume impregnation method to load the mixed solution on the alumina carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0194] Subsequently, conduct calcination, reduction, and carbonization reduction and crystal transformation treatment on the catalyst precursor. The specific steps are as follows:
[0195] (1) Calcination: the same as step 2(1) in Example 1;
[0196] (2) Reduction: the same as step 2(2) in Example 1;
[0197] (3) Carbonization reduction and crystal transformation: same as step (3) in Example 1.
[0198] The activated catalyst N was obtained. By ICP analysis, the weight percentage of metallic Co in the catalyst was 20.2 wt% (calculated as metal), and the weight percentage of promoter Cr was 3.1 wt% (calculated as metal). By HRTEM analysis, the particle size of the metal nanoparticles on the catalyst was distributed in the range of 20 - 40 nm.
[0199] 3. The catalyst evaluation method was the same as step 3 in Example 1.
[0200] Comparative Example 8
[0201] The composition of catalyst O was 20Co3Cr / Al2O3. Among them, the weight percentage of metallic Co was 20 wt%, and the weight percentage of promoter Cr was 3.0 wt%. Using commercially available alumina with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used were hydroxyethyl cellulose, ethylene glycol, and glycerol. The catalyst was prepared according to the following steps.
[0202] 1. Using commercially available alumina as the catalyst carrier, no pretreatment was carried out. The specific surface area of the commercially available alumina was measured by N2 physical adsorption to be 260 m 2 / g, the pore volume was 0.6 mL / g, and the pore size distribution was in the range of 5 - 70 nm.
[0203] 2. The preparation method of the catalyst was as follows:
[0204] Weighed 12.4 grams of cobalt nitrate hexahydrate and dissolved it in 5 grams of deionized water, 2.0 grams of chromium nitrate nonahydrate and dissolved it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol, and 0.1 gram of glycerol and dissolved them in 1 gram of deionized water. The three solutions were fully mixed evenly. Weighed 10 grams of activated carbon, and the mixed solution was loaded on the alumina carrier by the equal volume impregnation method. Left standing at room temperature for 10 hours, and dried in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0205] Subsequently, the catalyst precursor was subjected to calcination, reduction, and carbonization reduction and crystal transformation treatments. The specific steps were as follows:
[0206] (1) Calcination: same as step (1) in Example 1;
[0207] (2) Reduction: same as step (2) in Example 1;
[0208] (3) Carbonization reduction and crystal transformation: same as step (3) in Example 1.
[0209] The activated catalyst O was obtained. By ICP analysis, the weight percentage of metallic Co in the catalyst was 20.5 wt% (calculated as metal), and the weight percentage of the promoter Cr was 3.3 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst was in the range of 20 - 40 nm.
[0210] 3. The catalyst evaluation method was the same as that in Step 3 of Example 1.
[0211] Comparative Example 9
[0212] The composition of catalyst P was 20Co3Cr / Al2O3. Among them, the weight percentage of metallic Co in the catalyst was 20 wt%, and the weight percentage of the promoter Cr was 3.0 wt%. Using commercially available alumina with a particle size of 20 - 40 mesh as the carrier, the water-soluble organic substances used were hydroxyethyl cellulose, ethylene glycol, and glycerol. The catalyst was prepared according to the following steps.
[0213] 1. Using commercially available aluminum sesquioxide as the catalyst carrier, no pretreatment was carried out. The specific surface area of the commercially available alumina was measured by N2 physical adsorption to be 260 m 2 / g, the pore volume was 0.6 mL / g, and the pore size distribution was in the range of 5 - 70 nm.
[0214] 2. The preparation method of the catalyst was as follows:
[0215] Weigh 12.4 grams of cobalt nitrate hexahydrate and dissolve it in 5 grams of deionized water, 2.0 grams of chromium nitrate nonahydrate and dissolve it in 4 grams of deionized water, 0.1 gram of hydroxyethyl cellulose, 0.1 gram of ethylene glycol, and 0.1 gram of glycerol and dissolve them in 1 gram of deionized water. Mix the three solutions thoroughly. Weigh 10 grams of activated carbon, and use the equal-volume impregnation method to load the mixed solution on the alumina carrier. Let it stand at room temperature for 10 hours, and dry it in an oven at 60 °C for 12 hours to obtain the catalyst precursor.
[0216] Subsequently, the catalyst precursor was subjected to calcination and reduction treatments. The specific steps were as follows:
[0217] (1) Calcination: the same as (1) in Step 2 of Example 1;
[0218] (2) Reduction: the same as (2) in Step 2 of Example 1.
[0219] The activated catalyst H was obtained. By ICP analysis, the weight percentage of metallic Co in the catalyst was 20.5 wt% (calculated as metal), and the weight percentage of the promoter Cr was 3.3 wt% (calculated as metal). By HRTEM analysis, the particle size distribution of the metal nanoparticles on the catalyst was in the range of 20 - 40 nm.
[0220] 3. The catalyst evaluation method was the same as that in Step 3 of Example 1.
[0221] As can be seen from the data in Table 1, when using commercially available activated carbon, silicon carbide, ordered mesoporous carbon and other carbon-based materials as carriers without pretreatment, the catalyst performance is poor;
[0222] When no water-soluble organic matter is added or only one water-soluble organic matter such as hydroxyethyl cellulose is added during the preparation process, the particle size of the metal cobalt nanoparticles on the catalyst is large and the dispersion degree is low, resulting in poor reaction performance;
[0223] During the catalyst preparation process, the catalyst performance is significantly improved by using carbothermal reduction and crystal transformation treatment; the catalyst with carrier pretreatment, carbothermal reduction and crystal transformation treatment, and the addition of various water-soluble organic matters during the preparation process has excellent Fischer-Tropsch synthesis performance, and its catalytic reaction activity, C 5+ hydrocarbon selectivity and the proportion of C 10 ~C 17 hydrocarbons in the liquid phase products are significantly increased.
[0224] Table 1 shows the reaction performance of the syngas to jet fuel fraction hydrocarbons of the catalysts in Examples 1-7 and Comparative Examples 1-9
[0225]
[0226]
[0227] Reaction conditions: Slurry bed reactor, reaction temperature 220 °C, reaction pressure 3.0 MPa, syngas (H2 / CO = 2.0) space velocity 2000 h -1 , reaction time 24 hours.
Claims
1. A hydrocarbon catalyst for synthetic gas to aviation kerosene fraction, characterized in that, It is a supported catalyst with a carbon-based material as the carrier and metallic cobalt as the active component supported on the carrier. The weight of metallic cobalt accounts for 8.0 - 30.0 wt% (preferably 9.0 - 25.0 wt%, more preferably 11.0 - 24.0 wt%) of the weight of the catalyst; A promoter is also supported on the carrier. The weight of the promoter accounts for 0.6 - 4.0 wt% (preferably 0.6 - 3.5 wt%, more preferably 1.0 - 3.0 wt%) of the weight of the catalyst and is one or more of zirconium, chromium, manganese, nickel, zinc, and yttrium; The active component and the promoter are loaded onto the carrier by incipient wetness impregnation, and then the catalyst precursor is prepared into an activated metal catalyst through calcination, reduction, and carbonization reduction and transformation crystallization treatment. The specific preparation process is as follows: (1) Using the carbon-based material as the carrier, a mixed solution prepared from an aqueous solution composed of a soluble cobalt salt, a soluble promoter salt, and a water-soluble organic matter is impregnated on the carrier in an equal volume, and the catalyst precursor is obtained after drying; In the impregnation solution during the catalyst preparation process, the weight of the water-soluble organic matter accounts for 0.01 - 5.0 wt% (preferably 0.05 - 4.5 wt%, more preferably 0.08 - 4.0 wt%) of the weight of the carrier; the water-soluble organic matter contains two components. The first component is hydroxyethyl cellulose, and the second component is one or more of ethylene glycol, diethylene glycol, 1,2-propanediol, 1,3-propanediol, glycerol, 1,4-butanediol, xylitol, sorbitol, and pentaerythritol; the mass ratio of the first component to the second component is 1:1 - 1:10 (preferably 1:1 - 1:8, more preferably 1:1 - 1:5); (2) Calcination: The catalyst precursor is first calcined in an inert atmosphere at a calcination temperature of 150 - 450 °C (preferably 200 - 430 °C, more preferably 200 - 400 °C), a pressure of 0.1 - 0.6 MPa (preferably 0.1 - 0.5 MPa, more preferably 0.1 - 0.4 MPa), and a gas hourly space velocity of 300 - 1500 h -1 (preferably 300 - 1300 h -1 , more preferably 400 - 1000 h -1 ), and the calcination time is 6 - 30 hours (preferably 6 - 24 hours, more preferably 10 - 24 hours); (3) Reduction: After calcination, the catalyst precursor is subjected to reduction treatment in a hydrogen-containing atmosphere. The hydrogen-containing atmosphere is hydrogen or a mixture of hydrogen and an inert gas, and the volume content of hydrogen in the hydrogen-containing atmosphere is 1% to 100% (preferably 5% to 95%, more preferably 9% to 90%); the reduction temperature is 300 to 650 °C (preferably 300 to 550 °C, more preferably 350 to 500 °C), the pressure is 0.1 to 1.0 MPa (preferably 0.1 to 0.8 MPa, more preferably 0.2 to 0.7 MPa), and the gas hourly space velocity is 300 to 1500 h -1 (preferably 300 to 1300 h -1 , more preferably 400 to 1000 h -1 ), and the reduction time is 10 to 60 hours (preferably 10 to 50 hours, more preferably 15 to 45 hours); (4) Carbonization reduction and transformation crystallization: ① After the catalyst precursor is reduced, it is switched to a carbon monoxide-containing atmosphere for carbonization treatment. The carbon monoxide-containing atmosphere is a mixture of carbon monoxide and an inert gas. The volume content of carbon monoxide in the carbon monoxide-containing atmosphere is 1 to 100% (preferably 5% to 95%, more preferably 9% to 90%); the carbonization temperature is 150 to 350 °C (preferably 170 to 320 °C, more preferably 180 to 250 °C), the pressure is 0.5 to 5.0 MPa (preferably 1.0 to 4.5 MPa, more preferably 1.0 to 4.0 MPa), and the gas hourly space velocity is 500 to 3000 h -1 (preferably 500 to 2500 h -1 , more preferably 600 to 2500 h -1 ), and the carbonization time is 10 to 60 hours (preferably 10 to 50 hours, more preferably 15 to 45 hours); ② After carbonization, switch to a hydrogen-containing atmosphere for reduction treatment. The hydrogen-containing atmosphere is hydrogen or a mixture of hydrogen and an inert gas. The volume content of hydrogen in the hydrogen-containing atmosphere is 1-100% (preferably 5%-95%, more preferably 9%-90%); the reduction temperature is 150-350 °C (preferably 300-550 °C, more preferably 180-250 °C), the pressure is 0.5-5.0 MPa (preferably 1.0-4.5 MPa, more preferably 1.0-4.0 MPa), and the gas hourly space velocity is 500-3000 h -1 (preferably 500-2500 h -1 , more preferably 600-2500 h -1 ), and the reduction time is 10-60 hours (preferably 10-50 hours, more preferably 15-45 hours).
2. The catalyst according to claim 1, characterized in that, The carbon-based material is a carbon-based material with a nanoporous structure. The carbon-based material needs to be pretreated before use, and the pretreatment process includes the following steps: Using a commercially available carbon-based material with a pore size distribution of 0.1 - 80 nm as the raw material, including one or more of activated carbon, ordered mesoporous carbon, silicon carbide, and nitrogen-doped activated carbon with a nitrogen mass content of 3% - 20% (preferably 3% - 18%, more preferably 4% - 18%), the following treatment is carried out: (1) The carbon-based material is subjected to pore expansion treatment in a specific atmosphere: the treatment gas is one or more of oxygen, carbon monoxide, carbon dioxide, and water vapor, the treatment temperature is 400 - 800 °C (preferably 450 - 750 °C, more preferably 480 - 720 °C), the treatment pressure is 0.1 - 1.0 MPa (preferably 0.1 - 0.8 MPa, more preferably 0.2 - 0.7 MPa), and the treatment time is 1 - 24 hours (preferably 1 - 20 hours, more preferably 2 - 20 hours); (2) Modify the carbon-based material obtained in step (1): The solution for modification is an aqueous solution of one or more of hydrochloric acid, nitric acid, sulfuric acid, phosphoric acid, and ammonia with a mass concentration of 1% to 20% (preferably 1% to 18%, more preferably 3% to 18%). The weight ratio of the solution to the carbon-based material is 2:1 to 20:1 (preferably 3:1 to 20:1, more preferably 3:1 to 18:1). The treatment temperature is 40 to 100 °C (preferably 40 to 90 °C, more preferably 45 to 90 °C), and the treatment time is 1 to 24 hours (preferably 2 to 24 hours, more preferably 2 to 20 hours). (3) Wash and remove impurities from the carbon-based material obtained in step (2): The washing temperature is 20 to 100 °C (preferably 25 to 95 °C, more preferably 30 to 95 °C), wash until pH = 7, and obtain a carbon-based support after drying. The treated carbon-based material should meet the following requirements: The pore size distribution is 2 to 100 nm, and the proportion of the number of pores with a pore size of 5 to 25 nm reaches more than 70%.
3. The catalyst according to claim 1, wherein the soluble cobalt salt is one or more of cobalt nitrate, cobalt phosphate, cobalt acetate, cobalt citrate, and cobalt malate; the soluble promoter salt is one or more of nitrates, sulfates, phosphates, and citrates of one or more of zirconium, chromium, manganese, nickel, zinc, and yttrium.
4. The catalyst according to claim 1, wherein in step (1), using the carbon-based material as a support, impregnate the mixed solution prepared from an aqueous solution of a soluble cobalt salt, a soluble promoter salt, and a water-soluble organic matter on the support in an equal volume, and let it stand at room temperature for 6 to 18 hours (preferably 6 to 16 hours, more preferably 8 to 16 hours), then dry in an air atmosphere at a temperature of 40 to 100 °C (preferably 40 to 95 °C, more preferably 45 to 95 °C) for 6 to 24 hours (preferably 6 to 20 hours, more preferably 8 to 20 hours) to obtain a catalyst precursor.
5. The catalyst according to claim 1, wherein the inert gas is one or more of nitrogen, argon, and helium; the reactors used in steps (2), (3), (4) for roasting, reduction, and carbothermal reduction and phase transformation steps are fixed-bed reactors or fixed fluidized-bed reactors.
6. Use of the catalyst according to any one of claims 1 to 5 in the synthesis of aviation kerosene fraction hydrocarbons from syngas.
7. The application according to claim 6, characterized in that The reactor for synthesizing aviation kerosene fraction hydrocarbons from syngas is a fixed-bed reactor, a slurry-bed reactor or a fixed fluidized-bed reactor. The feed gas is syngas (a mixture of H2 and CO). Under the reaction conditions where the H2 / CO molar ratio is 1.0 - 4.0 (preferably 1.2 - 3.5, more preferably 1.5 - 3.5), the reaction temperature is 180 - 280 °C (preferably 180 - 260 °C, more preferably 190 - 250 °C), the pressure is 1.0 - 8.0 MPa (preferably 1.0 - 7.0 MPa, more preferably 1.5 - 7.0 MPa), and the gas hourly space velocity is 500 - 8000 h -1 (preferably 500 - 6000 h -1 , more preferably 800 - 6000 h -1 ), the reaction of synthesizing aviation kerosene fraction hydrocarbons from syngas is carried out.
8. The application according to claim 7, characterized in that The reaction tail gas and product are continuously discharged. The generated liquid product first collects its heavy components with a hot tank, and then collects its light components with a cold trap. The temperature of the hot tank is maintained at 110 to 130 °C, and the temperature of the cold trap is maintained at 0 to 5 °C.
Citation Information
Patent Citations
Hydrocarbon synthesizing method
CN101195553A
Preparation of fischer-tropsch catalysts
CN101616735A
Cobalt-based catalyst for Fischer-Tropsch synthesis and preparation method for cobalt-based catalyst
CN104785277A
High-dispersion heavy-hydrocarbon Fischer-Tropsch synthetic catalyst based on carbonization processing method and preparation method thereof
CN108246313A
Preparation method of cobalt-based catalyst for preparing oil from synthesis gas
CN112808275A